Princess in Love - Cabot, Meg (New York : HarperCollins, 2002)
In a series of humorous diary entries, a New York City ninth grader agonizes over her love life, final exams, and future role as the princess of Genovia.
Keywords: Princesses -- Fiction; Identity -- Fiction; Schools -- Fiction; Love -- Fiction; Diaries -- Fiction; Humorous Stories. -- Fiction; New York (N.Y.) -- Fiction